Directional spontaneous emission in a mono-mode waveguide with a circular cross section - S. Al-Awfi (Alexandria Engineering Journal)
Exploring the spontaneous emission control of an excited two-level atom interacting with the vacuum within a circular waveguide surrounded by a perfect electric conductor is the main objective of this work. This type of emission is dependent on the intrinsic properties of the emitter, such as the emitter’s transition frequency and dipole moment direction, as well as the surrounding electromagnetic environment. Due to being statistical in nature, the fields do not have a well-defined phase, and thus the emission is considered incoherent or in an uncontrollable direction. We propose an approach to direct the emission from an atom embedded in a circular waveguide. To achieve this, multimode waveguides should be excluded because the total emission is simply presented in three orthogonal directions. In contrast, with mono-mode waveguides, the single photon transports in a single-mode waveguide coupled to a cavity embedded with an atom. Thus, the electric dipole moment vector is forced to take the direction of the only mode in which it is allowed to propagate. Besides giving rise to a single value for the emission, this also provides a way to control direction. Such waveguides have already been produced by recent advances in microfabrication technology.